(untitled) (Scientific journal of the Fergana State University, 2025)
This study explores the impact of innovative pedagogical strategies on the development of professional competence in students within technical higher education, with a particular focus on the building and construction sector. It underscores the significance of incorporating individualized learning pathways, the establishment of scientific and educational centers, and the promotion of creativity and innovation in the learning environment. Furthermore, the research highlights the pivotal role of educators’ expertise in motivating students and preparing them for the challenges of the industry. The results indicate that an integrated and comprehensive educational approach, blending both theoretical knowledge and practical application, notably enhances student engagement, the acquisition of professional skills, and the preparedness of students to meet the evolving demands of the construction industry. However, challenges such as limitations in resources and the need for continuous professional development for educators present obstacles to the full implementation of these strategies.